Development of Mothers' Health Literacy: Findings From the KUNO-Kids Study - Maja Pawellek; Angela Köninger; Michael Melter; Michael Kabesch; Christian Apfelbacher; Susanne Brandstetter (SLACK Incorporated, 2023)
Background and Objective: The aim of this study was to analyze the longitudinal development of health literacy (HL) in a large cohort of new mothers in Germany and to investigate which determinants are associated with the initial HL level and with change over time. Methods: Longitudinal data from 1,363 mothers participating with their child in the KUNO-Kids Health Study was used; data were collected at birth of the child (baseline), after 6 and 12 months, using interviews and self-report questionnaires. The HL of mothers was assessed with the health care scale of the European Health Literacy Survey Questionnaire, which has 16 items on accessing, understanding, appraising, and applying health information in the health care setting. Latent growth curve models were used to analyze average trajectories and predictors of HL in the total sample and in the subgroup of first-time mothers. Key Results: HL values increased from baseline (M = 35.46, standard deviation [SD] = 7.34) over 6 months (M = 37.31, SD = 7.31) to 12 months (M = 38.01, SD = 7.41). The increase was statistically significant in the total sample (1.188, standard error [SE] = 0.087, p < .001) and in the subgroup of first-time mothers (1.357, SE = 0.113, p <. 001), with a steeper trajectory for mothers with lower HL at baseline. Several personal and situational variables were associated with HL at baseline (e.g., education, child health) and with its development (e.g., number of children). Conclusion: Overall, new mothers became slightly more health literate during their child's first year of life. However, some groups of mothers could benefit from support in developing HL skills even before childbirth. [HLRP: Health Literacy Research and Practice. 2023;7(1):e39-e51.] Plain Language Summary: We investigated how health literacy (that is the ability to find, understand, and apply health information) develops in new mothers in Germany. Mothers told us that this ability slightly improved during the child's first year of life. Some mothers still have difficulties in dealing with health information; these mothers should be supported even before childbirth.